(3GdJYdje GdEOGQj GdYQHj (B:s (3GdBaGb hGdJMOjGJ (B/s ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 1997)
(3GdEJLGgGJ hGdJZjQGJ GdYGdejI hGdEbdjejI aj ejGOjf GdEbJUGO hGdCYeGd hGfYcGSGJgG Ydi GdEOGQI(B- (3GdESJQGJjLjGJ GdehLgI HGdWdH aj GdJYdje GdEOGQj(B- (3eJWdHGJ GdJMhd Gdi GdESJQGJjLjGJ GdehLgI HGdWdH ef MjK BdjGJ hcjajI GMOGK GdJMhd(B.s
Keywords: (3GdJYdjes; (3GdJYdje GdEOGQjs; (3GdJYdje GdYQHjs